Clinical Features of Children with Retinoblastoma and Neuroblastoma. (10th July 2020) - Fang, Xiaolian; Wang, Huanmin; Ma, Xiaoli; Guo, Yongli; Yang, Wei; Hu, Shoulong; Qiu, Yue; Zhao, Junyang; Ni, Xin
Abstract : Purpose . Retinoblastoma and neuroblastoma are the most common malignant extracranial solid tumors in children. This study aimed to summarize the clinical features, especially the delayed diagnosis in children with retinoblastoma and neuroblastoma. Methods . In a single hospital-based case-control study, a retrospective cohort of 175 children with retinoblastoma and neuroblastoma diagnosed from January 2016 to January 2018 were reviewed. The state of enucleation in retinoblastomas and pathological prognosis in neuroblastomas were outcome indicators. Hereby, the patients were divided into two groups, and clinical features including age at presentation and delayed diagnosis were compared. Results . A total of 112 patients with retinoblastoma and 63 with neuroblastoma were included. In the retinoblastoma cohort, the median age at presentation was 17.2 months (0.3–110 months). The mean delay of diagnosis was 1.6 ± 2.3 months, and the rate of enucleation was 61.6%. Unilateral disease, the International Classification of Intraocular Retinoblastoma (IIRC) stage E, and delay of diagnosis over 2.5 months were independent risk factors of ocular outcomes. Notably, the risk of enucleation was increased by 474% when the delay was longer than 2.5 months. In the neuroblastoma cohort, the delay of diagnosis of the unfavorable histology (UH) group was longer than that of the favorable histology (FH) group (1.9 months vs. 1.4 months, P = .487 ). The levels of serum ferritin and neuron-specific enolase were higher in the UH group than in the FH group (P < .05 ). Conclusions . This study summarized the clinical features and diagnosis biomarkers of retinoblastoma and neuroblastoma patients in China. These results might help to focus on early detection and treatment in children with retinoblastoma and neuroblastoma.